FTA engages in the United Nations Food Systems Summit, contributes to public consultations of the UN Action Tracks, and proposes game-changing solutions that have been adopted by the UNFSS - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA proposed a set of game-changing solutions, contributed to public consultations of the UN Action Tracks, to dialogues and to debates in action tracks; significantly influencing the discussions and results.